Variation of Wood Density in Tropical Rainforest Trees - Djomo, Adrien N; Ngoukwa, Guylene; Zapfack, Louis; Chimi, Cédric D (Journal of Forests, 2017)
Measurement of wood density in Congo Basin forests are needed to reduce uncertainties on estimations of carbon stocks. The purpose of this study was to test vertical variation and temperature variation (80 °C, 105 °C) effects on wood density of species in a semi-deciduous forest of eastern Cameroon. Wood samples were collected on felled trees, at the base, middle of the trunk and on the branches in plots of 10 m x 10 m for trees <5 cm diameter, of 20 m x 10 m for trees with diameter between 5 and 10 cm and, of 20 m x 250 m for trees with diameter ≥ 10 cm. 162 trees with diameter between 1 cm and 146 cm were used. The highest wood density (0.912) was found in Ficus sp. and lowest (0.295) in Enantia chlorantha. Using 80 °C as temperature to estimate wood density increased the value of about 10% when compare to the reference temperature of 105 °C. A significant difference was observed between wood density of the base and the top of trees studied. 10 species did not have wood density reported in the Global Wood Density database. This study recommends further research on wood density to cover as many tree species as possible in the Congo Basin.